Infection Prevention in Chronic Kidney Disease/Dialysis/Transplant - Khalid, Myda; Nailescu, Corina (Journal of Pediatric Infectious Diseases, 2016)
Children with renal disorders including chronic glomerular conditions, chronic kidney disease, end-stage renal disease, and kidney transplant recipients have a higher infection risk. This review covers infection prevention in this population, with a focus on vaccination strategies.
Keywords: children; infection prevention; immunization; vaccines; chronic kidney disease; dialysis; kidney transplant; nephrotic syndrome; eculizumab